The development of a cryptoglandular Anal Fistula Core Outcome Set (AFCOS): an international Delphi study protocol. Issue 2 (March 2020) - Machielsen, A.J.H.M.; Iqbal, N.; Kimman, M.L.; Sahnan, K.; Adegbola, S.O.; Kleijnen, J.; Vaizey, C.J.; Grossi, U.; Tozer, P.J.; Breukink, S.O.
Purpose: Cryptoglandular anal fistula is a disorder with an incidence of around 1 per 5, 000 people per year in European countries. Many studies have been conducted to evaluate the effectiveness of interventions for anal fistula. However, there is considerable heterogeneity in the outcomes assessed and reported in these studies. This limits research quality and complicates evidence synthesis. A solution for heterogeneity in outcome reporting is the development of a Core Outcome Set (COS). This paper describes the protocol for the development of a European COS for Anal Fistula (AFCOS). Methods: The first step will be a systematic review of the literature to identify potential outcomes that may be included in the COS. Patient interviews will be conducted in The United Kingdom and The Netherlands to ensure that both clinician-important and patient-important outcomes are captured. The outcomes will be categorized using the COMET taxonomy and taken forward to a Delphi consensus exercise. In up to three web-based Delphi surveys the outcomes will be prioritized by patients, clinicians (surgeons, gastroenterologists, and radiologists), and (clinical) researchers. The responses will be summarized and reported anonymously in subsequent round(s) facilitating convergence to a consensus opinion. The final COS will be decided during a face-to-face consensus meeting with patients, clinicians, and (clinical) researchers. Discussion: This study protocol describes the development of a European COS for anal fistula to improve research quality, evidence synthesis, and patient care.